2013
DOI: 10.1111/jvim.12071
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Interpretation of Acid‐Base Abnormalities in 54 Adult Horses with Acute Severe Colitis and Diarrhea

Abstract: Background: The quantitative effect of strong electrolytes, pCO 2 , and plasma protein concentration in determining plasma pH and bicarbonate concentrations can be demonstrated with the physicochemical approach. Plasma anion gap (AG) and strong ion gap (SIG) are used to assess the presence or absence of unmeasured anions.Hypotheses: The physicochemical approach is useful for detection and explanation of acid-base disorders in horses with colitis. AG and SIG accurately predict hyperlactatemia in horses with col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 35 publications
2
24
1
5
Order By: Relevance
“…These findings emphasize the importance of identifying the presence of strong UAs by calculating SIG when applying the physicochemical approach. Additionally, this study highlights the role of strong ions in the acid–base status of calves with diarrhea, and indicates that replacement fluid therapy in animals with diarrhea should be aimed at resolving volume deficits, improving peripheral perfusion, and correcting [Na + ] and [Cl − ] imbalances …”
Section: Discussionmentioning
confidence: 82%
“…These findings emphasize the importance of identifying the presence of strong UAs by calculating SIG when applying the physicochemical approach. Additionally, this study highlights the role of strong ions in the acid–base status of calves with diarrhea, and indicates that replacement fluid therapy in animals with diarrhea should be aimed at resolving volume deficits, improving peripheral perfusion, and correcting [Na + ] and [Cl − ] imbalances …”
Section: Discussionmentioning
confidence: 82%
“…showed a strong correlation between SIG and plasma [ l ‐lac − ] in healthy horses. Similarly, a previous study of horses with diarrhea showed that SIG and AG had a very good sensitivity and specificity to predict important hyper‐ l ‐hyperlactatemia ( l ‐lac −  > 5 mmol/L) in horses with acute diarrhea 29. In this study, the AUC ROC analysis revealed that when the threshold of plasma [ l ‐lac − ] was 7 mmol/L, the sensitivity and the specificity of SIG to predict hyper‐ l ‐lactatemia were excellent.…”
Section: Discussionmentioning
confidence: 64%
“…Alternatively, SIG has shown an excellent correlation with [ l ‐lac − ] in healthy horses under exercise conditions,28 and horses with acute diarrhea 29. But, the sensitivity and specificity of AG and SIG to predict [ l ‐lac − ] in hospitalized foals is currently unknown.…”
mentioning
confidence: 99%
“…Based on the measured and calculated parameters, acid‐base imbalances were categorized using both the traditional and the quantitative strong ion approach according to the specifications presented in Table . The reference ranges used for the acid‐base parameters are reported in Table 3 . Device‐specific reference ranges were provided for Na + , Cl − , and K + concentrations.…”
Section: Methodsmentioning
confidence: 99%